La clandestinidad al revés durante la “Revolución Argentina”. El episodio de los tenientes peronistas (1966-1973) - Alejo Tolosa (Nuevo mundo - Mundos Nuevos, 2022)
The present work seeks to reconstruct the course of a group within the army known as "the Peronist lieutenants" during the period of the "Argentine Revolution" (1966-1973). Through the analysis of unpublished sources and interviews with its protagonists, I propose to describe this episode, its scope and how the intervention of the military justice had an impact on its incorporation into the Peronist movement. My hypothesis is that this episode constitutes a genuine expression of subordinate officers in the context of political-social conflict in the sixties and seventies and goes beyond the characterizations of the time about the internal currents of the army.